A global model for corrosion-induced cracking in prestressed concrete structures. (April 2016) - Dai, Lizhao; Wang, Lei; Zhang, Jianren; Zhang, Xuhui
Abstract: A global model is proposed in this study to predict prestressed concrete (PC) cracking induced by strand corrosion. The proposed model considers the three stages: micro-crack formations, cover cracking initiation, and crack width growth. The prestress and geometric properties of the strand have been incorporated into the prediction. Six PC beams were designed and accelerated toward corrosion-induced cracking. Observing the strands supported visual evidence of pitting corrosion and crevice corrosion. The effects of corrosion-induced crack on the failure of beams are analyzed. The proposed model is verified by the experimental results and this work presents the effects of parameters on corrosion-induced cracking. The results show that prestress has an adverse effect on corrosion-induced cracking. Prestress leads to a decrease in the critical corrosion loss at the three stages. This decrement becomes more noticeable with increasing cover and decreasing concrete tensile strength, but shows no remarkable changes with an increasing strand diameter and rust expansion ratio. Highlights: A global model for corrosion-induced cracking in PC structures is proposed. The prestress and geometric properties of the strand have been incorporated into the prediction. An accelerated corrosion test is performed to verify the corrosion-induced cracking model. The effects of parameters on corrosion-induced cracking are presented.